Speed-based target profit : planning and developing synchronous profitable operations - Posteuca, Alin (New York : Productivity Press, 2020)
Profitable production planning is and will remain an eternal challenge to ensuring the prosperity and dignity of companies in a global market. Even though there are different approaches to achieving the target profitability through productivity in the production planning stage, these approaches do not guarantee consistent planning, creation, and sustenance of synchronous profitable operations for multiannual and annual target profit. In feedback to this predicament, Alin Posteuc develops a new system called speed-based target profit (SBTP). SBTP is the profitable production management and manufacturing improvement system that approaches production planning to achieve unit speed of target profit for target products through manufacturing cost improvement and bottleneck profitability control for maximum takt time. Managers and practitioners within manufacturing companies will discover a practical approach for cost down and cash up by applying a powerful operational profitable production planning formula to meet profitability expectations through productivity based on strong leadership with the help of a specific system for feedforward, concurrent, and feedback control. Therefore, the SBTP system in this book presents a holistic approach to profitability for target products and the development of its own mechanism since the acceptance of each order from customers to achieve continuous synchronization of all manufacturing processes to market requirements, profitability management, and profitable production planning. The uniqueness of the book is reinforced by a detailed presentation of the successful application of the SBTP system in two case studies, as a way of life and a unit speed of target profit improvement ethos at all hierarchical levels, in two multinational manufacturing companies operating in highly competitive markets in order to address the synchronous profitable operations for both the sales increase scenario and the sales decrease scenario. By adopting the SBTP system, your company will be able to consistently achieve unit speed of target profit in the bottleneck process for fulfilling annual and multiannual target profit as a unique and effective way through a new profitable production planning paradigm that operates according to its own production system.
Figures. Tables. List of Abbreviations. Preface. About the Author. Introduction. Section I Understanding Speed-Based Target Profit. Chapter 1 Changing The Production Planning Paradigm. Chapter 2 Develop Your Speed-Based Target Profit Mechanism and Start to Live It. Section II Planning Synchronous Profitable Operations. Chapter 3 Support Striving for Speed-Based Target Profit. Chapter 4 Feedforward Control for Production Planning and Scheduling. Section III Developing Synchronous Profitable Operations. Chapter 5 Concurrent and Feedback Controls. Chapter 6 Speed-Based Target Profit Case Studies. Bibliography. Index.
OCLC-licensed vendor bibliographic record.
Keywords: Production planning; BUSINESS & ECONOMICS / General; BUSINESS & ECONOMICS / Leadership; BUSINESS & ECONOMICS / Management